Prediction and Prevention of High-Output Stoma After Colorectal Surgery - Marcos Almanza Ramírez; Mariana Damian Aldama; Daniela Gómez Gómez; Ana Isabel Cadena Carreón; Gustavo Quihuis García; Gabriel Hafner Vázquez Navarro (International Journal of Medical Science and Clinical Research Studies, 2026)
High-output stoma (HOS) is the most frequent functional complication after the construction of a diverting or terminal ileostomy in colorectal surgery, affecting roughly 15-30% of patients and accounting for a substantial proportion of unplanned readmissions for dehydration, electrolyte derangement and acute kidney injury. Although the condition is largely preventable, its diagnosis is still delayed in routine practice because output measurement is inconsistent and diagnostic thresholds remain heterogeneous (1000-2000 mL/24 h). This narrative review summarizes current evidence on the definition, pathophysiology, risk factors, predictive models and preventive strategies for HOS after colorectal surgery. Consistently reported predictors include male sex, extremes of age, alcohol intake, perioperative use of angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, postoperative intestinal obstruction or ileus, intra-abdominal sepsis, hypoalbuminemia, leukocytosis and electrolyte abnormalities. Published prediction tools - from decision-tree models to multivariable nomograms - achieve areas under the curve of 0.79-0.91 but share important methodological limitations, including single-center retrospective design, inconsistent outcome definitions and scarce external validation. Preventive care is best delivered as a bundle: preoperative risk stratification and nutritional optimization, review of renin-angiotensin blockade and diuretics, systematic measurement of stoma output, early exclusion of sepsis and outlet obstruction, restriction of hypotonic fluid with glucose-saline rehydration solutions, stepwise antimotility and antisecretory therapy, structured education with output diaries, and protocol-driven follow-up after discharge. Adoption of a uniform definition and prospective multicenter validation of risk models are the priorities for future research.